2000
DOI: 10.1530/eje.0.1430091
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical function in patients with macrometastases of the adrenal gland

Abstract: Objective: Metastases of the adrenal gland are a frequent ®nding in patients with malignant tumors like bronchogenic carcinoma or breast cancer. Only limited and con¯icting data on adrenocortical function in these patients are available. Design: Cross-sectional study. Methods: We investigated the impact of adrenal macrometastases on adrenocortical function in a series of 28 tumor patients using the ACTH 1±24 stimulation test and dexamethasone suppression test. Seven normal controls (Con), eleven patients witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 32 publications
0
31
0
1
Order By: Relevance
“…2,3 Of note, metastasis to the adrenal glands rarely causes adrenal insufficiency, and occurs only if metastatic disease is bilateral, with extensive damage to the adrenal glands. 4 Without adequate steroid replacement therapy, this was an invariably fatal condition in the time of Addison, with almost all patients dying within the initial 5 years of diagnosis. The discovery of cortisone by Hench, Kendall, and Reichstein in the late 1940s improved the outlook on patients with adrenal insufficiency dramatically, and initial data suggested that life expectancy was normalized.…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…2,3 Of note, metastasis to the adrenal glands rarely causes adrenal insufficiency, and occurs only if metastatic disease is bilateral, with extensive damage to the adrenal glands. 4 Without adequate steroid replacement therapy, this was an invariably fatal condition in the time of Addison, with almost all patients dying within the initial 5 years of diagnosis. The discovery of cortisone by Hench, Kendall, and Reichstein in the late 1940s improved the outlook on patients with adrenal insufficiency dramatically, and initial data suggested that life expectancy was normalized.…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…Even in two cases of large bilateral metastases, there was no adrenal insufficiency in these patients. Adrenal insufficiency, a state which is often suspected in cases of metastases to both adrenal glands, is in fact a rare symptom in such patients [24].…”
Section: Prace Oryginalnementioning
confidence: 99%
“…We have interpreted prior reports (2,3) as demonstrations that the stress of cancer enhances cortisol production and dexamethasone resistance in proportion to the extent of tumor burden. We suspect that cancer patients with bilateral adrenal metastases have greater stress-induced cortisol production than patients with unilateral adrenal metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the premortem diagnosis of adrenal insufficiency due to adrenal metastases is uncommon (1). Past studies have reported that the initial response to metastatic involvement of the adrenals is an increase in cortisol release, which is resistant to dexamethasone suppression (2,3). Thus, the typical cancer patient with metastases to adrenal glands has increased cortisol levels.…”
Section: Introductionmentioning
confidence: 99%